Excessive neutrophil extracellular trap formation induced by Porphyromonas gingivalis lipopolysaccharide exacerbates inflammatory responses in high glucose microenvironment - Yue Tong; Yue Tong; Yue Tong; Yue Xin; Yue Xin; Yue Xin; Lanqing Fu; Lanqing Fu; Lanqing Fu; Jia Shi; Jia Shi; Jia Shi; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionNeutrophil extracellular trap (NET) is a novel defense strategy of neutrophils and found to be induced by Porphyromonas gingivalis (P. gingivalis) lipopolysaccharide (LPS) or high glucose. The aim of this study was to investigate the roles and mechanisms of NET formation in high glucose inflammatory microenvironment.MethodsNETs induced by 1 μg/ml P. gingivalis LPS and/or 25 mM glucose were visualized using a fluorescence microscopy and the levels of extracellular DNA were determined by a microplate reader. The bactericidal efficiency of NETs was assessed by quantifying the survival P. gingivalis in neutrophils. The levels of NLRP3 and IL-1β in THP-1 derived-macrophages, and the expressions of p-PKC βII, p-MEK1/2, p-ERK1/2, ORAI1 and ORAI2 in neutrophils were detected by Western blot. Moreover, levels of intracellular Ca2+ and reactive oxygen species (ROS) in neutrophils were explored by flow cytometry.ResultsP. gingivalis LPS enhanced the formation of NETs and increased the levels of extracellular DNA in high glucose microenvironment (p < 0.05). Compared with normal glucose inflammatory microenvironment, quantities of extra- and intracellular viable P. gingivalis in neutrophils exposed to NETs induced in high glucose inflammatory one were increased (p < 0.05) and the expressions of NLRP3 and IL-1β were dramatically increased in macrophages co-cultured with NETs from high glucose inflammatory microenvironment (p < 0.05). In addition, levels of ROS, intracellular Ca2+, p-PKC βII, p-MEK1/2, p-ERK1/2, ORAI1 and ORAI2 were increased in neutrophils stimulated with both high glucose and P. gingivalis LPS compared with the single stimulus groups (p < 0.05).DiscussionIn high glucose inflammatory microenvironment, formation of NETs was enhanced via oxidative stress, which failed to reverse the decreased bactericidal capacity in high glucose microenvironment, and instead aggravated the subsequent inflammatory responses.